Who decides what: Spatial issues in environmental decisions. Issue 5 (2022) - De Angelis, Elena; Carnevale, Claudio; Turrini, Enrico; Volta, Marialuisa; Ferrari, Fabrizio; Maffeis, Giuseppe; Guariso, Giorgio; Pisoni, Enrico
Abstract: An integrated modelling approach is used in this work to assess the differences in defining air quality policies in spatial domains of different extensions. The tools used, SHERPA and RIAT+, are public domain and allow to rapidly define the emission scenario of the European area under examination and to solve a multi-objective problem to trade-off air quality improvement versus the costs of implementing the pollutant abatement measures. The territory considered is Northern Italy and the pollutant analysed in PM2.5, which is largely of secondary origin. The study demonstrates the importance of a proper definition of the administrative and physical boundaries of the air pollution problem, which may determine higher costs when the correct scale of decisions is missed.